Should Monsters, Mutants, and Ghosts Vote? Monstrous Croatian Lyric and the Principle of Democratic Equality - Vuković, Tvrtko (Poznańskie Studia Slawistyczne, 2019)
The paper starts from the assumption that Croatian modern lyric, from Matoš to Maleš, is haunted by various monsters, phantoms and mutants, and possessed by ghosts. Phantasmal hair speaks, the body changed by illness acquires autonomy, bird-men, space-twins and angels inhabit the humanized world, the dead seek eternity, the turtle measures itʼs own existence in relation to space and time, and Jesus-fish according to the degree of its own evolutionary transformation, while language cyborgs and hybrid beings are born. The lyric about monsters is itself a monstrous discourse. In this discourse human existence is necessarily contaminated by the abhuman and the parahuman, language includes its own mutations, and the encounter with meaning depends on the ultimate deformation, hybridization and disappearance of meaning. Thus, in the very center of our humanity, in the artistic form that determines the measure of the humanity of our community, questions about what is humane and inhumane, how to determine the boundary between them, and is not the general understanding of humanity always-already determined by oneʼs own inhuman or a-human are raised. Looking at a series of lyric texts, the paper will analyze these relationships and subsequently show their possible political and legal effects. I will refer to theoreticians who read the lyric as a linguistic event and performative type of utterance (J. Culler, P. de Man, B. Johnson, and others) and to thinkers who, to say it simply, perceive the ideas of equality, law and justice as phantasmal, mutated, scandalous or monstrous democracy (G. Agamben, J. Rancière, J. Derrida, J-L. Nancy and others).